Metaplacenticeras subtilstriatum (Jimbo, 1894) (Cephalopoda: Ammonoidea) from the St Lucia Formation (Cretaceous), Zululand - Klinger, H; Kennedy, W (1990)
An ammonite identified as Metaplacenticeras subtilstriatum (Jimbo, 1894) was recovered from a borehole in Zululand. It represents the first record of this genus and species outside the Pacific Realm, and permits a precise Late Campanian (Cretaceous) date for that section of the core. -Authors